Endoscopic ultrasound‐guided choledochoduodenostomy using a thin stent delivery system in patients with unresectable malignant distal biliary obstruction: A prospective multicenter study. Issue 3 (18th December 2018) - Itonaga, Masahiro; Kitano, Masayuki; Hatamaru, Keiichi; Tamura, Takashi; Nuta, Junya; Kawaji, Yuki; Takenaka, Mamoru; Minaga, Kosuke; Kudo, Masatoshi; Ogura, Takeshi; Higuchi, Kazuhide; Chiba, Yasutaka
Abstract : Background and Aim: When endoscopic retrograde cholangiopancreatography (ERCP) fails in patients with malignant distal biliary obstruction, endoscopic ultrasound‐guided choledochoduodenostomy (EUS‐CDS) is an alternative. It has high technical and clinical success rates, but also has high adverse event rates. This prospective cohort study was aimed to evaluate the clinical efficacy and safety of EUS‐CDS with our newly developed partially covered self‐expandable metal stent with a thin delivery system. Methods: Patients consisted of all consecutive patients in three tertiary referral centers with unresectable malignant distal obstruction in whom ERCP failed and in whom EUS‐CDS with the thin delivery system was selected as the second‐line approach. Rates of clinical success, technical success, technical success in cases not requiring fistulous tract dilation, adverse events, and stent dysfunction were determined. Results: In the 20 patients, technical and clinical success rates were 95.0% (19/20) and 100% (19/19), respectively. In 31.6% (6/19), the delivery system was successfully inserted into the bile duct without requiring a fistulous‐tract dilatation device. These patients had significantly shorter procedure times than patients requiring fistulous‐tract dilatation (12.7 ± 3.1 vs 23.2 ± 2.1 min; P  <   0.01). One patient (5.0%) who required fistulous dilation had an adverse event, which was managed conservatively. There were no procedure‐related deaths. During follow up, four patients (21.1%) developed stent dysfunction. Reintervention was successful in all cases. Conclusions: The EUS‐CDS approach had 95% technical and 100% clinical success rates, with adverse events reported in 5% of cases. EUS‐CDS may become safer if efforts are made to avoid the dilation step (UMIN 000023938).